A pilot effectiveness study of the Enhancing Parenting Skills (EPaS) 2014 programme for parents of children with behaviour problems: study protocol for a randomised controlled trial - Williams, Margiad Elen (Trials, 2015)
BACKGROUND: The Enhancing Parenting Skills (EPaS) 2014 programme is a home-based, health visitor-delivered parenting support programme for parents of children with identified behaviour problems. This trial aims to evaluate the effectiveness of the EPaS 2014 programme compared to a waiting-list treatment as usual control group. METHODS/DESIGN: This is a pragmatic, multicentre randomised controlled trial. Sixty health visitors will each be asked to identify two families that have a child scoring above the clinical cut-off for behaviour problems using the Eyberg Child Behaviour Inventory (ECBI). Families recruited to the trial will be randomised in a 1:1 ratio into an intervention or waiting-list control group. Randomisation will occur within health visitor to ensure that each health visitor has one intervention family and one control family. The primary outcome is change in child behaviour problems as measured by the parent-reported ECBI. Secondary outcomes include other measures of child behaviour, parent behaviour, and parental depression as measured by parent-reports and an independent observation of parent and child behaviour. Follow-up measures will be collected 6-months after the collection of baseline measures. DISCUSSION: This is the first rigorous evaluation of the EPaS 2014 programme. The trial will provide important information on the effectiveness of a one-to-one home-based intervention, delivered by health visitors, for pre-school children with behaviour problems. It will also examine potential mediating (improved parent behaviour and/or improved parental depression) and moderating (single parent, teenage parent, poverty, low education level) factors. TRIAL REGISTRATION: Current Controlled Trials ISRCTN06867279 (18 June 2014)